A rule-based method for automated surrogate model selection. (August 2020) - Jia, Liangyue; Alizadeh, Reza; Hao, Jia; Wang, Guoxin; Allen, Janet K.; Mistree, Farrokh
Abstract: Surrogate models have been widely used in engineering design because of their capability to approximate computationally complex engineering systems. In practice, the choice of surrogate models is extremely important since there are many types of surrogate models, and they also have different hyper-parameters. Traditional manual selection approaches are very time-consuming and cannot be generalized. To address these challenges, an evolutionary algorithm (EA)-based approaches are proposed and studied. However, they lack interpretability and are computationally expensive. To address these gaps, we create a rule-based method for an automatic surrogate model selection called AutoSM. The drastic increase in the selection pace by pre-screening of surrogate model types based on selection rule extraction is the scientific contribution of our proposed method. First, an interpretable decision tree is built to map four critical features, including problem scale, noise, size of sample and nonlinearity, to the types of surrogate model and select the promising surrogate model; then, a genetic algorithm (GA) is used to find the appropriate hyper-parameters for each selected surrogate model. The AutoSM is tested with three theoretical problems and two engineering problems, including a hot rod rolling and a blowpipe design problem. According to the empirical results, using the proposed AutoSM, we can find the promising surrogate model and associated hyper-parameter in 9 times less than other automatic selection approaches such as concurrent surrogate model selection (COSMOS) while maintaining the same accuracy and robustness in surrogate model selection. Besides, the proposed AutoSM, unlike previous EA-based automatic surrogate model selection methods, is not a black box and is interpretable.